(3GdPNjQI aj JbQjX GdSjQIs - (3eMeO Hf fGgV Hf eMeO Hf MSf, TeS GdOjf GdLgfj GdMdHj,J (B841 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdebUhO , GdYXje GdehLhO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B122s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B151 s
(3eUOQ GbJfGA GdCUd (B:s
(3QVG QGeHhQ ai GdgfO (B(3628) s
Keywords: (3GdJGQjNs